2003
DOI: 10.1002/pmic.200300537
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomics of neurokinin B in the placenta indicates a novel role in regulating cytotrophoblast antioxidant defences

Abstract: Neurokinin B (NKB) has recently been demonstrated to be secreted from the placenta in abnormally high amounts in preeclampsia (PE) and to cause hypertension in rats, suggesting it may be a mediator of some pathophysiological features of PE. It is also known that NKB receptors exist in the placenta. To determine the effect of high levels of NKB on the placenta, we have performed proteomics on five separate preparations of cultured purified human term cytotrophoblast cells. The results showed a statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…3C and D). Accordingly, evidence that CypA functions as an antioxidant has been recently accumulated (16,(30)(31)(32). Our previous study also showed that overexpressed CypA removed ROS generated by cyclosporin A (17).…”
Section: Discussionmentioning
confidence: 89%
“…3C and D). Accordingly, evidence that CypA functions as an antioxidant has been recently accumulated (16,(30)(31)(32). Our previous study also showed that overexpressed CypA removed ROS generated by cyclosporin A (17).…”
Section: Discussionmentioning
confidence: 89%
“…9 Up to now, only a few proteomic studies have been performed on the placental tissue or cell lines and the relationship between the placental proteome changes and pregnancy-related disorders, such as pregnancy loss and preeclampsia. 8,[10][11][12][13][14][15][16][17] Considering the scarcity of the published studies on the proteome changes during fetus development, the present study aimed to compare the total placental proteome differences between the normal first-and third-trimester human placentas. In order to fulfill this goal, placental proteins from normal first-and third-trimester human placentas were extracted and subjected to 2D-PAGE.…”
Section: Introductionmentioning
confidence: 99%
“…Lung proteins were separated by twodimensional gel electrophoresis, as detailed by Sawicki et al (2003). Protein (200 g) was applied to 11 cm IPG (linear pH gradient range 3-10) strips (six samples on six separate strips for each treatment group; Bio-Rad), with rehydration, for 16 -18 hr at 20°C.…”
Section: Dimensional Gel Electrophoresismentioning
confidence: 99%